Réflexions autour de la notion d’homophobie: succès politique, malaises conceptuels et application empirique - Chamberland, Line; Lebreton, Christelle (Nouvelles Questions Féministes, 2012)
Après en avoir retracé rapidement la genèse, cet article rapporte les principales critiques adressées au concept d’homophobie, notamment son réductionnisme qui tend vers des explications de nature psychologique ainsi que l’éviction de la hiérarchie des sexes/genres. Nous discutons ensuite deux pistes théoriques permettant de contourner les limites précédemment identifiées. La première examine le potentiel de l’approche intersectionnelle. La seconde voie invite à une redéfinition du concept d’homophobie, lui reconnaissant une portée exclusivement descriptive, et non plus en tant que concept explicatif, justifiant ainsi sa subordination au concept d’hétérosexisme qui offre une perspective systémique. Nous examinons ces concepts en fonction de leur capacité à rendre compte de l’oppression des lesbiennes.
Keywords: 1900-1999; 1970-1979; 1980-1989; 2000 à aujourd'hui; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; homophobie; hétérosexisme; identités LGBTQIA2+; intersectionnalité; lesbianisme; phi2030; philosophie; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; états-unis

Polyrhythmic dance currents: Race multiculturalism and the montreal dance community - Templeton, Melissa (Université de Californie à Riverside, 2012)
This dissertation examines African and African Diaspora concert dance in Montreal in relation to Canadian multicultural policies and Québec nationalism. The multiple layers of colonization and various waves of immigration to Québec have made the province a unique nation with its own complex history of racial construction, quite unlike the racial histories of the U.S. or the rest of Canada (though still greatly informed by these racial paradigms). In the debates that arise in Québec over multiculturalism, language is often seen as the main cultural component in need of preservation. However, this focus on language often masks other elements at play in these cultural debates, in particular, how "race" informs notions of cultural belonging in Québec. A focus on African Diaspora dance in Montreal (Québec's largest and most demographically varied city) helps bring racial construction to the fore for two reasons. First, language differences do not distinguish Québec's Black community from the white French-Canadian majority as Québec's Black population is comprised mainly of French-speakers, and accordingly, studying Montreal's African Diaspora reduces the significance of linguistic difference. Second, concentrating on dance practices helps identify how the Montreal public interprets bodies and their cultural meanings. By analyzing the public support and critical reception of African Diaspora dance practices in Montreal, this dissertation examines how racial difference is constructed through multicultural rhetoric, policies, and debates about dance; it also suggests that dance practitioners have the ability to change and inform these constructed identities and the social landscape that frames them. To conduct this research, I use archival material along with personal interviews and participant-observer ethnography to examine: the early visits of Les Ballets Africains to North America (with a particular focus on Montreal); the Montreal-based company Les Ballets Jazz; the 1999 Montreal festival Afrique: Aller/Retour; and the work of Contemporary African dance choreographer Zab Maboungou. With these subjects, my projects contributes a partial history of African Diaspora dance in Montreal and analyzes the effectiveness and the shortcomings of Canadian Multiculturalism on this community.
Keywords: 1900-1999; amérique du nord; amériques; approches et analyses; canada; corps; corps féminin; danse; diaspora africaine; discipline; montréal; multiculturalisme; mémoires/thèses; philosophie; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques